COST-BENEFIT ANALYSIS OF MASS VACCINATION PROGRAMS EXEMPLIFIED BY MEASLES VACCINATION - MA. Faghih (Tehran University of Medical Sciences, 1973)
In planning any vaccination program, priority should be given to such programs within the country's overall health plan. This judgment is made on the basis of indices on morbidity, mortality, vulnerability, feasibility and cost-benefit/effectiveness analyses. The application of mathematical / epidemiological models and the use of simulation and goal -seeking techniques and monograms are of great value and will provide information on health benefits which are either quantifiable or excessively difficult to quantify. To illustrate, two examples from Iran's measles vaccination program are cited. In a five-year , country -wide program with 37% coverage and $3,828,136 cost ($1.09/unit), 214,733 cases were prevented and 37,274 lives were saved, resulting in $10,736,650 case-treatment, 1,708,878 life-years and 644,200 school-days saved . The estimated cost of one prevented case is $18.62. A four-year specific campaign covering 55% of the at-risk labor-insured population , costing $59,444 (0.85/unit) resulted in 1,728 cases prevented, 61 lives(2,867 years) and 5,214 school -days and $152.327 case-treatment saved. The cost of one prevented case is estimated at $34.20.